Association between HLA-DQB1 and cervical dysplasia in Vietnamese women. Issue 3 (1st April 2006) - Lema, C.; Fuessel-Haws, A. L.; Lewis, L. R.; Rady, P. L.; Lee, P.; Turbat-Herrera, E. A.; He, Q.; Nguyen, L. T.; Tyring, S. K.; Dao, D. D.
Abstract : Host genetic background seems to play a key role in cervical carcinogenesis as only a small subset of women infected with high-risk human papillomaviruses (HPVs) develop cervical cancer. The rate of cervical cancer in Vietnamese women is notably high. To explore the association of human leukocyte antigen (HLA)-DQB1 alleles, HPV infection, and cervical dysplasia in this population, cervical smears were obtained from 101 women attending the obstetrics and gynecology clinic of Da Nang General Hospital in Vietnam. Besides the Papanicolaou test, HPV and HLA-DQB1 genotyping were performed using cervical smear DNA. Additionally, a subset of 30 blood samples was used as the gold standard for HLA genotyping. HLA-DQB1 alleles showed no association with HPV infection status. However, a positive association with cervical dysplasia was found for HLA-DQB1*0302 ( P = 0.0229, relative risk (RR) = 4.737) and HLA-DQB1*0601 ( P = 0.0370, RR = 4.038), whereas HLA-DQB1*0301 ( P = 0.0152, RR = 0.221) was found negatively associated. The low diversity of HLA-DQB1 alleles, wide spectrum of HPV genotypes, and high prevalence of HPV 16 and HPV 18 observed in the study population suggest a permissive/susceptible genetic background that deserves further research. Total concordance of HLA-DQB1 genotyping results between blood and cervical cells confirms the potential value of cervical smears as an effective tool for the development of cervical cancer biomarkers.